로봇 냉각을 위한 수냉식 냉각판의 성능 평가 - 이석원; 강상우; 황규대; 김서영; 이광훈 (대한설비공학회, 2008)
The increase of system weight due to installation of cooling devices adds electrical and mechanical loads of humanoid robot, and in return, results in much heat. Therefore, the weight of cooling system is a critical issue for robot cooling. In this study, we propose non-metallic cold plates to deal with such problems. We compare thermal performances between one metallic cold plate and five different types of non-metallic cold plates. A metallic cold plate is totally made of copper. Five non-metallic PC (polycarbonate) cold plates, which are designed to reduce the overall weight of robot cooling system, are composed of a polycarbonate cover with different types of base plate. The overall heat transfer coefficients per unit mass and thermal resistances are obtained for the cold plates. The metallic cold plate shows the best thermal performance. It is interesting to note that the PC cold plate with an aluminum base plate with 18 channels shows the best overall heat transfer coefficient per unit mass. Most polycarbonate cold plates display fairly comparable thermal performance with more reduced system weight compared to the metallic cold plate.